The impact of live broadcasts of breaking news on the audience of Iraqi satellite channels (Journal of Al-farahidi's Arts, 2026)
The study aimed to shed light on the impact of live broadcast of breaking news on the audience of Iraqi satellite channels. The study followed the descriptive analytical approach through a questionnaire on a random sample of the audience of Iraqi satellite channels. Due to the difficulty of conducting a comprehensive census, the study used the simple random sampling method to obtain the study data. The number of study sample members was 237 individuals who answered the questions of the electronic questionnaire form. The study reached a set of results, the most important of which are: the existence of a strong direct correlation with statistical significance between live broadcast of breaking news and the audience of Iraqi satellite channels at a significance level of 0.01. The study recommended the need to work on increasing the awareness of community members of the positive role that Iraqi satellite channels can play in disseminating breaking news.